The Tracking of Moist Habitats Allowed Aiphanes (Arecaceae) to Cover the Elevation Gradient of the Northern Andes - Sanín, María José; Borchsenius, Finn; Paris, Margot; Carvalho-Madrigal, Sara; Gómez Hoyos, Andrés Camilo; Cardona, Agustín; Arcila Marín, Natalia; Ospina, Yerson; Hoyos-Gómez, Saúl E.; Manrique, Héctor Favio; Bernal, Rodrigo (Frontiers in Plant Science, 2022)
The topographic gradients of the Tropical Andes may have triggered species divergence by different mechanisms. Topography separates species’ geographical ranges and also offers climatic heterogeneity, which could potentially foster local adaptation to specific climatic conditions and result in narrowly distributed endemic species. Such a pattern is found in the Andean centered palm genus Aiphanes. To test to which extent geographic barriers and climatic heterogeneity can explain distribution patterns in Aiphanes we sampled 34 out of 36 currently recognized species in that genus and sequenced them using Sanger sequencing and/or sequence target capture sequencing. We generated Bayesian, likelihood, and species-tree phylogenies, with which we explored climatic trait evolution from current climatic occupation. We also estimated species distribution models, to test the relative roles of geographical and climatic divergence in their evolution. We found that Aiphanes originated in the Miocene in Andean environments and possibly in mid-elevation habitats. Diversification is related to the occupation of the adjacent high and low elevation habitats tracking high annual precipitation and low precipitation seasonality (moist habitats). Different species in different clades repeatedly occupy all the different temperatures offered by the elevation gradient from 0-3000 m in different geographically isolated areas. A pattern of conserved adaptation to moist environments is consistent among clades. Our results stress the evolutionary roles of niche truncation of a wide thermal tolerance by physical range fragmentation, coupled with water-related niche conservatism, to colonize the topographic gradient.Diversification is related to the occupation of the adjacent high and low elevation habitats tracking high annual precipitation and low precipitation seasonality (moist habitats). Different species in different clades repeatedly occupy all the different temperatures offered by the elevation gradient from 0-3000 m in different geographically isolated areas. A pattern of conserved adaptation to moist environments is consistent among clades. Our results stress the evolutionary roles of niche truncation of a wide thermal tolerance by physical range fragmentation, coupled with water-related niche conservatism, to colonize the topographic gradient.